16th International Conference on Meteorology, Climatology and Atmospheric Physics—COMECAP 2023 2023
DOI: 10.3390/environsciproc2023026118
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Public Health: Air Pollution and Chronic Diseases

Pinelopi Petropoulou,
Ioli Artopoulou,
Ioannis Kalemikerakis
et al.

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Under specific plausible conditions, an earlier study demonstrated that results from time series studies equal estimates from a dynamic population, similar to a cohort study, when each individual’s survival experience is summarized as the daily number of deaths ( 70 ). These findings further emphasize two considerations: (i) short- and long-term effects are quantitatively similar and variations in observed effects are likely the result of differences in follow-up times between the time series and cohort designs and (ii) relying solely on the time series estimates of mortality (evaluating just a few days of exposure) to estimate the burden from wildfire PM 2.5 will likely underestimate the effects because the dose-response function fails to include the accumulated contribution of PM 2.5 to chronic diseases such as atherosclerosis, asthma, lung function decrements, and diabetes ( 40 , 71 74 ), all of which could contribute to higher mortality risk and push some individuals into the susceptible ranges where acute events would accelerate their death.…”
Section: Discussionmentioning
confidence: 99%
“…Under specific plausible conditions, an earlier study demonstrated that results from time series studies equal estimates from a dynamic population, similar to a cohort study, when each individual’s survival experience is summarized as the daily number of deaths ( 70 ). These findings further emphasize two considerations: (i) short- and long-term effects are quantitatively similar and variations in observed effects are likely the result of differences in follow-up times between the time series and cohort designs and (ii) relying solely on the time series estimates of mortality (evaluating just a few days of exposure) to estimate the burden from wildfire PM 2.5 will likely underestimate the effects because the dose-response function fails to include the accumulated contribution of PM 2.5 to chronic diseases such as atherosclerosis, asthma, lung function decrements, and diabetes ( 40 , 71 74 ), all of which could contribute to higher mortality risk and push some individuals into the susceptible ranges where acute events would accelerate their death.…”
Section: Discussionmentioning
confidence: 99%
“…And we need to focus more on air quality management in educational spaces [10,11]. When carbon dioxide exceeds a certain concentration, it causes drowsiness and adversely affects not only the health of students but also their concentration in lectures [12,13]. To prevent this, confined spaces with many people need periodic ventilation as much as possible.…”
Section: Introductionmentioning
confidence: 99%